Reviewing research on regional development in the AI era — new there(s), new actors, and an old call “from cluster to process” - Hautala, Johanna (Geographical society of Finland, 2024)
The aim of this review is to present the current state and suggest next steps for research on AI-related regional development. Based on thematic content analysis of 37 articles in key journals of regional development and economic geography, I answer where, by whom, and how AI-related regional development takes place. The results reveal a strong narrative of increasing concentration and regional polarization, and a less considered narrative of the potential of dispersion that also enables the development of remote regions. I suggest advancing research through identifying ‘new there(s)’ as virtual and augmented realities, AI as a new actor, and a methodological step from ‘cluster to process’ to investigate the everyday spatial processes of creating knowledge and being creative with AI that catalyze regional development.
Keywords: regional development; clusters; artificial intelligence; innovation policy; fi=Aluetiede|en=Regional Studies|